Experimental study on the seismic behavior of corroded reinforced concrete walls in an artificial climate corrosion environment. (1st February 2022) - Zheng, Yue; Zheng, Shan-Suo; Yang, Lu; Dong, Li-Guo; Ruan, Sheng; Ming, Ming
Highlights: The environmental chamber were used to simulate the natural corrosion environment, and the corroded reinforced concrete wall specimens were obtained. The corrosion phenomenon of corroded reinforced concrete wall specimens was analyzed, and the effects of corrosion degree, axial load ratio, horizontal rebar spacing on the failure mode and seismic behavior of corroded reinforced concrete wall were studied. The effects of corrosion degree, axial load ratio and horizontal rebar spacing on the shear performance of corroded reinforced concrete walls were studied. Calculation formulas for the bearing capacity and deformation of the corroded reinforced concrete wall considering the influence of design parameters were proposed based on the experimental results. Abstract: Previous research shows that corrosion of reinforcement caused by chloride penetration is the key factor that weakens the seismic performance of reinforced concrete (RC) structures. Both environmental erosion and squat walls have so far been underexplored, which makes it difficult to evaluate the seismic performance of RC shear wall structures subjected to chloride salt erosion. Accordingly, in this paper, eight squat RC wall specimens with an aspect ratio of 1.0 are subjected to accelerated corrosion tests in an artificial climate environment and pseudostatic tests, and the effects of corrosion degree, axial compression ratio and horizontal distribution of rebar spacing on the seismic performance of corroded squat RC wall specimens are investigated. The results show that the corrosion morphology of rebar in an artificial climate environment is similar to that in a natural environment. With an increasing corrosion level, the bearing capacity, deformation capacity and energy dissipation capacity of the specimen degrade gradually, but the deformation capacity degrades to a greater degree. At the same time, the average shear deformation and the proportion of shear deformation in the total deformation of the specimen under different load conditions increase gradually, which manifests in a transformation of the failure mode of the corroded specimen from flexural-shear failure to shear-dominated failure. Additionally, the increase in density of horizontally distributed rebar has a more significant influence on the deformation capacity and energy dissipation capacity of the corroded specimens than on the bearing capacity. Finally, the existing equation is revised based on the test data, and the calculation equation for the characteristic point parameters of the corroded squat wall skeleton curve, including the corrosion degree, the axial compression ratio and the horizontal distributed reinforcement ratio, is established.